Manejo del dolor Osteoarticular en Pacientes Caninos con un Extracto Activo de CBD (Monografía) (2024)
Degenerative joint disease (DJD) in dogs, a concern both emotionally and clinically for owners and veterinarians, has sparked growing interest in exploring more effective therapeutic options. This study focused on investigating the therapeutic potential of cannabidiol (CBD) for pain management in dogs with DJD. Through a methodology that included the collection and classification of information from secondary sources, studies published between 2010 and 2022 addressing the pharmacokinetics and dynamics of CBD in this population were selected. The results revealed that CBD interacts with receptors of the endocannabinoid system (ECS), reducing the perception of pain and inflammation in joints affected by DJD. Additionally, it was observed that CBD preserves cartilage integrity and provides sustained pain relief, with therapeutic advantages over conventional analgesic therapy due to its safety profile and comprehensive ability to address underlying DJD symptoms.